Effect of tethering on the structure-property relationship of TPU-dual modified laponite clay nanocomposites prepared by ex-situ and in-situ techniques - Mishra, Ananta K.; Chattopadhyay, Santanu; Rajamohanan, P. R.; Nando, Golok B. (Polymer, 2011)
Novel Thermoplastic Polyurethane (TPU)-dual modified Laponite clay nanocomposites were prepared by ex-situ and in-situ techniques. Two types of modified clays used in this work differ from each other by the number of active functional groups (tethering). Modified nanoclays are characterized by FTIR, Solid State NMR, XRD and TGA. Structural differences in the modified clays lead to novel tubular, elliptical and spherically aggregated morphologies of clays together with the hard segments of TPU. Changes in such morphology result in the difference in segmental relaxation, mechanical and rheological properties of the nanocomposites. In-situ prepared nanocomposites register inferior properties as compared to their ex-situ counterparts. The percent improvement in tensile strength and elongation at break of the ex-situ prepared nanocomposites with the modified clay having lesser tethering are found to be 67% and 208%, respectively. Thermal stability is enhanced by 35 degrees C as compared to that of the neat TPU. (C) 2010 Published by Elsevier Ltd.
Keywords: Dual modification; Nanocomposites; Thermoplastic polyurethane

Structure-property of thermoplastic polyurethane-clay nanocomposite based on covalent and dual-modified laponite - Mishra, Ananta K.; Rajamohanan, P. R.; Nando, Golok B.; Chattopadhyay, Santanu (Journal of Computational and Theoretical Nanoscience, 2011)
Modification of surface of clay platelets by ionic and covalent modification techniques renders it to be easily dispersed in polymers like, Thermoplastic Polyurethane (TPU). Only ionic or covalent modification techniques in isolation are not sufficient to achieve uniform nanoscale dispersion of Laponite (synthetic hectorite nanoclay) in TPU. Hence, the dual modification of Laponite (both ionic and covalent) is performed and the effects of the modification on the morphology, thermal and rheological behaviors of the TPU-modified clay nanocomposites have been studied. The degree of exfoliation of clay platelet in TPU matrix is found to be higher for dual functionalized nanoclays compared to their singly modified counterparts. Interestingly, dual modified Laponite clays prepared by using two different techniques (ionic followed by covalent and covalent followed by ionic) exhibit different morphology and properties. The dual modified clays significantly alter the equilibrium morphology of TPU. The storage modulus of the dual modified Laponite-TPU nanocomposite in the glassy region (at -60 degrees C) land in the rubbery region (+98 degrees C) is improved by 172.8% and 85%, respectively as compared to the neat TPU. Similarly, the onset of degradation is found to be enhanced by 28.7 degrees C as compared to the neat TPU.
Keywords: Dual modification; Laponite Nanocomposite; Morphology; Structure-Property; Thermoplastic polyurethane